(3QSGdI GdSGFd hGdeLjH hQhVI fRgI GdCOjHs
(3ChdgG (B:s
(3GdMeO ddg hCTgO Cf SjOfG hehdGfG eMeO YHOg hQShdg s
(3BNQgG (B:s
(3gPG eGjSQ Gddg ai PcQg hUdi Gddg Ydi SjOfG hehdGfG eMeO s
(3Cdag HQSe GdMGLH CHj RcQjG jMji Hf RjGf ai GdOhdI GdeHfjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs